1995
DOI: 10.1177/0146167295214009
|View full text |Cite
|
Sign up to set email alerts
|

Group Versus Individual Training and Group Performance: The Mediating Role of Transactive Memory

Abstract: The task performance of laboratory work groups whose members were trained together or alone was investigated. At an initial training session, subjects were taught to assemble transistor radios. Some were trained in groups, others individually. A week later, subjects were asked to recall the assembly procedure and actually assemble a radio. Everyone performed these tasks in small work groups, each containing three persons of the same gender. Subjects in the group training condition worked in the same groups whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
719
3
10

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 836 publications
(756 citation statements)
references
References 29 publications
13
719
3
10
Order By: Relevance
“…Teams characterized by a lack of group longevity experience greater difficulty recognizing and integrating their knowledge for efficient task completion (Liang, Moreland, & Argote, 1995). Nevertheless, the relationship of team stability with team learning and performance is a matter of some debate in the literature (Edmondson, Bohmer, & Pisano, 2001 (Edmondson, Winslow, Bohmer, & Pisano, 2003;Moreland & Levine, 1989).…”
Section: Team Stability: Towards a Mediation Model Of Leadership And mentioning
confidence: 99%
“…Teams characterized by a lack of group longevity experience greater difficulty recognizing and integrating their knowledge for efficient task completion (Liang, Moreland, & Argote, 1995). Nevertheless, the relationship of team stability with team learning and performance is a matter of some debate in the literature (Edmondson, Bohmer, & Pisano, 2001 (Edmondson, Winslow, Bohmer, & Pisano, 2003;Moreland & Levine, 1989).…”
Section: Team Stability: Towards a Mediation Model Of Leadership And mentioning
confidence: 99%
“…Seven measures from four studies were categorized as cognitive outcomes that indicate some type of cognitive change attained by the trainees. Example cognitive measures are ratings of interpositional knowledge (knowledge an individual holds with respect to the roles and needs of other team members under the demands of specific task situations; Cannon-Bowers, Salas, Blickensderfer, & Bowers, 1998), development of shared mental models (Marks, Sabella, Burke, & Zaccaro, 2002), and procedural recall and memory differentiation (Liang, Moreland, & Argote, 1995). Subjective task-based skill outcomes.…”
Section: Team Effectiveness Measuresmentioning
confidence: 99%
“…Twenty measures from nine studies were categorized as objective task-based skill outcomes. Examples of objective measures are team performance (as indicated by points earned in a simulation game; Day et al, 2005), tons per manshift (Buller, 1988;Buller & Bell, 1986), accuracy and speed , and assembly errors and assembly time (Liang et al, 1995). Teamwork skill outcomes.…”
Section: Team Effectiveness Measuresmentioning
confidence: 99%
“…Because of the differentiated nature of teams requiring cognitive mechanisms to enhance coordination, one specific form of team training, cross-training, might be especially beneficial as it increases interpositional knowledge regarding team members' roles and responsibilities. Moreland and his colleagues (e.g., Liang et al, 1995;Moreland et al, 1998) found that teams that trained together developed a stronger transactive memory system, while Cannon-Bowers, Salas, Blickensderfer, and Bowers (1998) Team Cognition Development 16 found that cross-training was positively related to mental model development. Cross-training may therefore act as a partial substitute for initial role identification behaviors, providing teams with a basic understanding of each other's domains and jump-starting the development of team cognition (Marks et al, 2002).…”
Section: Discussionmentioning
confidence: 99%